2004
DOI: 10.1017/s1431927604882187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humidity on the Microstructures of Electrospun Polystyrene Nanofibers

Abstract: In recent years, many researchers have been studied and developed the nanofibers which have a large specific surface area and a small pore size. The polymer nanofibers are being used or finding uses in filtration, biomedical applications including wound dressings as structural elements in artificial organs, and reinforced composites. Thus these special needs have stimulated recent studies and renewed interest in the process, quantitative technical and scientific information regarding process and product charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…This agrees with a recent study that the change in RH condition can change the nanofiber thickness, depending on the chemical nature of the polymer, polymer‐solvent interaction, which leads to different evaporation rates . The increase in RH typically causes an increase in fiber size and formation of surface features of spun fibers derived from nonaqueous solvent, for example, poly(acrylonitrile)/DMF, polysulfone/DMF , and polystyrene/THF . The interplay between crystallization and discharging rate of the solution jets was proposed as the origin of this behavior.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This agrees with a recent study that the change in RH condition can change the nanofiber thickness, depending on the chemical nature of the polymer, polymer‐solvent interaction, which leads to different evaporation rates . The increase in RH typically causes an increase in fiber size and formation of surface features of spun fibers derived from nonaqueous solvent, for example, poly(acrylonitrile)/DMF, polysulfone/DMF , and polystyrene/THF . The interplay between crystallization and discharging rate of the solution jets was proposed as the origin of this behavior.…”
Section: Resultssupporting
confidence: 90%
“…During the spinning, the applied surface charge on solution jets is interfered with and captured by moisture droplets in the surroundings, as water has higher conductivity than air. This lowers the opportunity to split the solution jets to become thinner fiber, leading to formation of larger fibers, for semicrystalline copolymers . In addition, it was reported that RH conditions affected fiber properties differently, depending on the polymer structure and interactions, due to complex interactions between the nonsolvent (water), the hygroscopic solvent, and the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined that while the surface tension of polymer solution had linear correlation with the critical voltage of process initiation, throughput was dependent on electric conductivity [10]. Additionally, when relative humidity, which is an ambient condition, is increased, mean fiber diameters on the web are increased [11].…”
Section: Process Parameters Of Electrospinningmentioning
confidence: 99%
“…The increase in humidity resulted in formation of circular pores in smaller quantities and a further increase resulted in non uniform pores. Kim et al 90 observed that when the relative humidity is increased, mean fibre diameter is also increased. Polyamide-6 was electrospun at temperatures ranging from 25 to 60˚C and it was found that at higher temperatures the fibre diameter decreased which was attributed to the decrease in viscosity of the solution at higher temperatures.…”
Section: Ambient Parametersmentioning
confidence: 99%